2016
DOI: 10.1097/md.0000000000003193
|View full text |Cite|
|
Sign up to set email alerts
|

The Application of Liver Stiffness Measurement in Residents Without Overt Liver Diseases Through a Community-Based Screening Program

Abstract: The application of liver stiffness measurement (LSM) by transient elastography (TE) in general population remains to clarify. This cohort study aimed to examine the usefulness of TE and to identify factors associated with significant liver fibrosis in community-based population.We conducted a hepatitis screening program in 2 remote villages of Southern Taiwan. All residents participated voluntarily and received questionnaire evaluation, blood tests, abdominal sonography, and LSM by TE. Residents with any one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Consistent with previous reports, the findings of this study demonstrates that high BMI, high AST levels, low platelet counts, and low albumin levels are independent risk factors for significant liver fibrosis assessed through TE . The mechanism underlying higher LSM values in patients with higher BMI values has not been well documented.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with previous reports, the findings of this study demonstrates that high BMI, high AST levels, low platelet counts, and low albumin levels are independent risk factors for significant liver fibrosis assessed through TE . The mechanism underlying higher LSM values in patients with higher BMI values has not been well documented.…”
Section: Discussionsupporting
confidence: 83%
“…We assessed the risk factors to be associated with significant liver fibrosis (LSM > 7 kPa) assessed through TE and compared with the APRI, which is a validated serum marker of liver fibrosis. Significant liver fibrosis was defined as an APRI score of >0.7 .…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal waist circumference was linked to higher prevalence of NAFLD, in the study done by Cheng PN et al 22 Authors also found significant correlation of liver stiffness with waist circumference (p<0.01).…”
Section: Discussionmentioning
confidence: 81%
“…For sensitivity analysis, we defined increased CAP as more than 248 dB/m . LSM ≥ 7 kPa was considered to indicate significant fibrosis, according to previous reports …”
Section: Methodsmentioning
confidence: 99%
“…14 LSM ≥ 7 kPa was considered to indicate significant fibrosis, according to previous reports. 12,15…”
Section: Key Pointsmentioning
confidence: 99%